Subsidizing extra jobs: promoting employment by taming the unions - Andreas Knabe; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the subsidization of extra jobs in a general equilibrium framework. While the previous literature focuses on symmetric marginal employment subsidies where firms are rewarded when they increase employment but punished when they reduce their workforce, we consider an asymmetric scheme that only rewards employment expansion. This changes the incidence substantially. In the asymmetric case without punishment, it becomes less costly for firms to lay off a substantial fraction of their workforce when trade unions raise wages. This tames the unions, which causes wage moderation and raises aggregate employment and welfare. For moderate subsidy rates, all unions prefer to restrain their wage claims. At sufficiently high subsidy rates, labor market conditions improve so much that some unions enforce higher wages and let their firms shrink. This displacement of firms might have a negative impact on employment and welfare.
Keywords: H25; J38; J68; 330; marginal employment subsidies; unemployment; general equilibrium; Lohnsubvention; Beschäftigungseffekt; Arbeitslosigkeit; Lohnpolitik; Allgemeines Gleichgewicht; Theorie